Influence of ethnicity on cyclin-dependent kinase inhibitor efficacy and toxicity: A systematic review and meta-analysis - Roberto Buonaiuto; Aldo Caltavituro; Margherita Tafuro; Alessandra Longobardi; Giuliana Pavone; Pierluigi De Santis; Roberta Caputo; Carmine De Angelis; Lucia Del Mastro; Fabio Puglisi; Mario Giuliano; Grazia Arpino; et al. (Breast)
Background: The combination of cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) with endocrine therapy (ET) is the standard of care for patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-) advanced breast cancer (aBC). While the efficacy and safety profiles of CDK4/6i and ET have been extensively evaluated in phase II and III trials worldwide, it remains unclear whether the response to CDK4/6i and toxicity profile vary among Asian and non-Asian patients. Therefore, we aimed to assess the treatment efficacy of ET with and without CDK4/6i by comparing outcomes in Asian and non-Asian subgroups included in these clinical trials. In addition, we evaluated the toxicity profiles of the treatments by estimating the risk of treatment-related adverse events (AEs). Methods: We conducted a meta-analysis including the most recent randomized trial data systematically searched from PubMed, Embase, Web of Science, Cochrane CENTRAL (from inception to May 31st, 2024) or presented in abstracts or oral presentations at the ESMO, ASCO, and SABCS international congresses. We included studies comparing CDK4/6i (palbociclib, ribociclib, abemaciclib, dalpiciclib) + ET versus placebo + ET. Progression-free survival (PFS) and overall survival (OS), hazard ratios (HR), and 95 % confidence intervals (CI) were extracted for the two subgroups of interest. To evaluate the treatment-related toxicity profiles, we extracted the number of side effects to estimate the risk of treatment-emergent AEs. Results: Eleven studies (n = 5129) were included in this meta-analysis. The addition of CDK4/6i to ET consistently improved PFS in both Asian (HR = 0.52, 95 % CI 0.47–0.60; p < 0.001) and non-Asian (HR = 0.58, 95 % CI 0.52–0.64; p < 0.001) groups. Similarly, the combination of CDK4/6i + ET led to an OS improvement in both Asian (HR = 0.75, 95 % CI 0.62–0.91; p = 0.003) and non-Asian (HR = 0.81, 95 % CI 0.73–0.89; p < 0.001) patients. The risk of treatment related toxicity was higher in the CDK4/6i + ET arm in both Asian and non-Asian groups. Interestingly, a numerically higher rate of treatment-related hematological toxicity was observed in Asian patients, although no significant interethnic difference was found in the relative risk of these events. Conclusions: The combination of CDK4/6i and ET significantly improves PFS and OS compared to ET alone in both Asian and non-Asian patients with HR+/HER2-aBC. Although the magnitude of benefit appears to be independent of ethnicity, future clinical trials should devise a standardized method for stratifying patients by ethnicity to more effectively assess potential differences in treatment benefits. Systematic review registration: PROSPERO registration number: CRD42024543217.